Monitoring cure in epoxies containing carbon nanotubes with an optical-fiber fresnel refractometer - Dimopoulos, Athanasios; Buggy, Stephen J.; Skordos, Alexandros A.; James, Stephen W.; Tatam, Ralph P.; Partridge, Ivana K. (Wiley, 2009)
Fresnel refractometry was used to follow the changes in the refractive index during the isothermal curing of a simple difunctional epoxy resin, a commercial formulated multifunctional epoxy blend, and the same two resin systems modified by the addition of multiwalled carbon nanotubes. The refractive index change, monitored via an embedded optical fiber, was correlated with the degree of cure established from isothermal differential scanning calorimetry measurements. A good correlation was established in all cases, indicating the potential of the technique to be used for online cure monitoring in thermosetting resin carbon nanocomposites.
Keywords: curing of polymers; nanocomposites; phase separation; refractive index; sensors